Influence of Social Media on Students' Business Interest at A Young Age - Hutabarat, Imran; Azzahra, Nadia; Sitepu, Putri Azhra (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
The objective of this study is to determine and analyze the impact of social media on the business interest of students at a young age. Primary data was collected through surveys using questionnaires distributed to a sample of 40 respondents. The gathered data was then subjected to analysis using SPSS software. The results indicated that the null hypothesis (H0) was accepted. This suggests that there is indeed an influence of social media on the business interest of students at a young age. In more specific terms, the data revealed that social media accounts for 75.7% of the observed influence on students' business interest during their early years. These findings provide insights into the significant role that social media plays in shaping the entrepreneurial interests of young students